Investigating the Effect of Dissolved Oxygen on Rotifers of Chakki Talab, Bodhan, Telangana, India - Vasudha Lingampally; V. R. Solanki; D. L. Anuradha; S. Sabita Raja (New Visions in Biological Science Vol. 3, 2021)
The purpose of this study was to look at the diversity and abundance of rotifers in Chakki talab, Bodhan, Telangana, in relation to dissolved oxygen. Rotifer distribution and diversity is influenced by deteriorating quality of water in freshwater ecosystems and eutrophication. From October 2015 to September 2016, rotifers from seven genera were studied, and their density was altered by a little shift in dissolved oxygen levels. The eutrophic state of Chakki talab was shown by the dominance of the genera Brachionus and Keratella.